2012
DOI: 10.1063/1.4765070
|View full text |Cite
|
Sign up to set email alerts
|

Effective large-area free-standing graphene field emitters by electrophoretic deposition

Abstract: Large area graphene field emitters were fabricated using electrophoretic deposition. By varying the deposition time, we were able to fabricate emitters with varied field enhancement factors. The turn-on field increased when the deposition time increased, and it was observed that a monolayer of graphene flakes covered on the substrate gave the best results. The low emission turn-on field obtained from the graphene field emitters was attributed to the random orientation of graphene flakes which give protruded ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Most of the studies [15,29,49,71,119,144,147,153,154] have reported that electrophoretically deposited GRM sheets lie parallel to the surface of their underlying electrode which produce a flat surface morphology. However, several studies [39,68,91,103,105,106,136,146,155,156] have reported the EPD of GRM sheets to occur with a perpendicular or random orientation to the electrode surface, leading to a rough surface with protruding graphene edges. Orientation may relate to dynamic effects during electrophoresis, including specific effects of charging salts (see Section 6.2 (v)), but is probably also strongly influenced by capillary effects during drying, and hence, the solvent surface tension and drying method.…”
Section: Wrinkles Surface Roughness and Graphene Edgesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies [15,29,49,71,119,144,147,153,154] have reported that electrophoretically deposited GRM sheets lie parallel to the surface of their underlying electrode which produce a flat surface morphology. However, several studies [39,68,91,103,105,106,136,146,155,156] have reported the EPD of GRM sheets to occur with a perpendicular or random orientation to the electrode surface, leading to a rough surface with protruding graphene edges. Orientation may relate to dynamic effects during electrophoresis, including specific effects of charging salts (see Section 6.2 (v)), but is probably also strongly influenced by capillary effects during drying, and hence, the solvent surface tension and drying method.…”
Section: Wrinkles Surface Roughness and Graphene Edgesmentioning
confidence: 99%
“…For example, electrodes for electrochemical double layer supercapacitors rely on high structural porosity as well as a large interlayer separation of GRM sheets to allow effective electrolyte access and to maximise the active surface area for charge storage [15,63,96,124,143]. On the other hand, field emission of electrons at low voltages requires a high surface roughness and a predominance of well distributed, individualised GRM edges [39,85,91,92,101,[144][145][146]. In contrast, a low surface roughness and high film bulk density are favoured for solid lubricant coatings [76] or barrier layers.…”
Section: Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…Some of the properties of graphene such as high aspect ratio, presence of abundant edges along with its excellent conductivity make it an ideal candidate for use in fuel cell 66,126 , Li-ion batteries 65,127,128 , supercapacitor 90,91 and field emission sources 131,132 .…”
Section: Ar Plasmamentioning
confidence: 99%
“…4,5 Electrophoretic deposition (EPD) is an economical and versatile processing technique that has been applied in deposition of films in recent years. [6][7][8][9] Wu et al had prepared GP emitters with EPD and compared it to emitters made by directly coating GP powder onto conductive tape, thus proving the effectiveness of EPD for field emission applications. 6 Koh fabricated large area GP field emitters using EPD and obtained the low turn on field emitters with varied field enhancement factors.…”
Section: Field Emission Performance Enhancement Of Au Nanoparticles Dmentioning
confidence: 98%